The Girl with the Dragon Tattoo (Millennium Trilogy 1) - Stieg Larsson (New York Alfred A. Knopf, 2008)
A sensation across Europe-millions of copies sold. A spellbinding amalgam of murder mystery, family saga, love story, and financial intrigue.It's about the disappearance forty years ago of Harriet Vanger, a young scion of one of the wealthiest families in Sweden . . . and about her octogenarian uncle, determined to know the truth about what he believes was her murder.It's about Mikael Blomkvist, a crusading journalist recently at the wrong end of a libel case, hired to get to the bottom of Harriet's disappearance . . . and about Lisbeth Salander, a twenty-four-year-old pierced and tattooed genius hacker possessed of the hard-earned wisdom of someone twice her age-and a terrifying capacity for ruthlessness to go with it-who assists Blomkvist with the investigation. This unlikely team discovers a vein of nearly unfathomable iniquity running through the Vanger family, astonishing corruption in the highest echelons of Swedish industrialism-and an unexpected connection between themselves.It's a contagiously exciting, stunningly intelligent novel about society at its most hidden, and about the intimate lives of a brilliantly realized cast of characters, all of them forced to face the darker aspects of their world and of their own lives.
Keywords: Psychological thriller